2023
DOI: 10.3389/fmed.2023.1225648
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life 1 year after hospital discharge in unvaccinated pregnant women with COVID-19 respiratory symptoms: a prospective observational study (ODISSEA-PINK study)

Luigi Vetrugno,
Alessia Sala,
Cristian Deana
et al.

Abstract: IntroductionLittle is known about Quality of Life within the first court of unvaccinated COVID-19 pregnant women exposed to the pandemic stressor. Primary aim of this study was to evaluate 1 year after hospital discharge HRQoL in a cohort of COVID-19 unvaccinated pregnant patients with COVID-19.Methodsin this prospective observational study, all COVID-19 positive pregnant women at any gestational age, admitted to the Obstetric Department at the University Hospital of Udine, Italy, from 1 March 2020 to 1 March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It is reported that patients who were admitted due to acute respiratory infection still have decreased QoL 1 year after hospital discharge. Future studies are warranted to evaluate the long-term QoL following gynecology surgery, which potentially addresses invaluable factors impacting QoL (21). Our study had a relatively slow accrual due to the study population being limited to those willing to complete QoL surveys at perioperative visits which may have led to bias in patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that patients who were admitted due to acute respiratory infection still have decreased QoL 1 year after hospital discharge. Future studies are warranted to evaluate the long-term QoL following gynecology surgery, which potentially addresses invaluable factors impacting QoL (21). Our study had a relatively slow accrual due to the study population being limited to those willing to complete QoL surveys at perioperative visits which may have led to bias in patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…NRDS is a disease caused by direct or indirect lung injury leading to lung inflammation, significantly affecting the respiratory system and jeopardizing the lives of affected infants ( 1 , 2 ). It can occur during intrauterine development, the birthing process, and after birth.…”
Section: Introductionmentioning
confidence: 99%